Family-Sourced Early Intervention Programs to Optimize Communication Development of Children with Multiple Disabilities - Maulidina, Citra Ashri; Taboer, Mohammad Arif; Jaya, Indra; Lianty, Leliana; Amani, Dwi Aisyah; Kairunisa, Shabila (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
Communication is a fundamental skill that must be fulfilled for all humans, including individuals with multiple disabilities. With communication, individuals with multiple disabilities can interact and participate with the environment so that they are not isolated. This study aims to formulate a family-sourced early intervention program to optimize the communication development of students with multiple disabilities in accordance with children's needs, so that families can hopefully become a support system in supporting their children's communication development. This research uses research methodology design and development design and development research (D DR), where in the first year researchers formulate programs based on needs in the field. The results showed that there are three family-sourced early intervention programs to optimize communication of individuals with multiple disabilities.